Pengabdian Masyarakat Tentang Personal Hygiene Di Lembaga Pemasyarakatan Kelas II A Pekanbaru - Syukaisih Syukaisih; Elmia Kursani; Alhidayati Alhidayati; Dita Novia (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Personal hygiene is an action to maintain one's cleanliness and health for physical and psychological well-being, lack of self-care is a condition where a person is unable to carry out hygiene care for himself. Seeing this, personal hygiene is defined as personal hygiene which includes all activities aimed at achieving body hygiene including washing, bathing, caring for hair, nails, teeth, and gums, and cleaning the genital area. If someone is sick, usually less attention to personal hygiene. This happens because they think that cleanliness is a trivial problem, even though if it is not paid attention to it it can affect personal health problems in terms cleanliness which will lead to skin diseases. The correctional institution is a correctional business unit that accommodates, treats, and fosters prisoners. A skin disease that usually occurs in prisoners is scabies. This is due to the condition of the correctional facilities not being fully optimal, the habits are not clean and personal hygiene is not maintained.